Analisis Komparatif Penyebaran Konten Korban Kecelakaan Tanpa Sensor Menurut Hukum Pidana Islam dan UU ITE - Sarifah A.I.T Sigalingging; Nofiardi Nofiardi (Lembaga Yasin AlSys, 2026)
The widespread dissemination of uncensored videos or photographs of accident victims through social media raises legal, ethical, and humanitarian issues because it has the potential to violate privacy, cause psychological trauma to victims’ families, and degrade the dignity of victims. This study aims to examine the regulation of the criminal offense of disseminating uncensored videos or photographs of accident victims according to Jarimah Ta’zir and Law Number 1 of 2024 concerning Electronic Information and Transactions, as well as to compare the regulations and sanctions in the two legal systems. This study used library research with a normative juridical approach through the examination of relevant written legal materials. The primary data sources included Law Number 1 of 2024 concerning Electronic Information and Transactions, particularly Article 27 paragraph (1), as well as Islamic legal literature on Jarimah Ta’zir. The secondary data sources included legal books, scientific journals, undergraduate theses, and other scholarly works. The results showed that the dissemination of uncensored videos or photographs of accident victims is an act that violates norms of decency and harms human dignity. In Islamic criminal law, this act constitutes a reprehensible act that can be categorized as Jarimah Ta’zir, whereas in Indonesian positive law it can be examined through the provisions of the Electronic Information and Transactions Law concerning content that violates decency. This study affirms similarities in the orientation toward protecting human dignity, as well as differences in the legal basis, forms of liability, and nature of sanctions between Islamic criminal law and Indonesian positive law. The implications of this study strengthen the importance of law enforcement and digital ethics literacy in preventing the dissemination of uncensored content involving accident victims in the digital space.